Bank consolidation and credit concentration in Brazil (1995-2004) - Daniel B. de Castro Almeida; Frederico G. Jayme (CEPAL Review, 2008)
Since monetary stabilization in 1994, bank consolidation has been gathering pace in Brazil as part of a global concentration trend following bank deregulation processes. This article analyses the effect of bank concentration on lending in Brazil in the period 1995-2004, distinguishing two stages and estimating panel data for Brazil’s 27 federative units. The results support the hypothesis that the process of consolidation in the Brazilian banking sector has an adverse effect on lending, which mainly harms the less developed regions of the country.